2009
DOI: 10.1080/17457300903308308
|View full text |Cite
|
Sign up to set email alerts
|

Are we there yet? Canada's progress towards achieving road safety vision 2010 for children travelling in vehicles

Abstract: This study examines safety seat use among Canadian children and evaluates child safety seat use relative to the national policy for child occupant safety, Road Safety Vision 2010. Using a probability sample, roadside observations of car safety seat use were collected from May to October of 2006 for 13,500 children aged from birth to 9 years in 10,084 vehicles at 182 sites in nine Canadian provinces and one territory. Observations revealed that 89.9% of Canadian children were restrained in some type of restrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 15 publications
2
22
0
1
Order By: Relevance
“…Two hundred survey sites across Canada were randomly selected according to a multi-stage stratified sampling plan based on the sampling design for the National Seat Belt Survey in 2001 (Transport Canada, 2001). The sampling design for this survey has been reported in greater detail in a previous paper (Snowdon et al, 2009a(Snowdon et al, , 2009b. This survey used the population density of children based on 2004 census data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two hundred survey sites across Canada were randomly selected according to a multi-stage stratified sampling plan based on the sampling design for the National Seat Belt Survey in 2001 (Transport Canada, 2001). The sampling design for this survey has been reported in greater detail in a previous paper (Snowdon et al, 2009a(Snowdon et al, , 2009b. This survey used the population density of children based on 2004 census data.…”
Section: Methodsmentioning
confidence: 99%
“…The primary objective of these surveys was to obtain national estimates of child restraint which has been reported in a previous paper (Snowdon et al, 2009a(Snowdon et al, , 2009b. This paper focuses on the secondary objective which compares the estimates of restraint use between the two survey methods and discusses the advantages and disadvantages of the two methodologies.…”
Section: Introductionmentioning
confidence: 98%
“…The data analyzed in this example are based on a Canadian child safety seats survey described in Snowdon et al (2009). The main objective of the survey was to measure whether children traveling in vehicles on Canadian roads are correctly restrained in safety devices that are appropriate for their ages, weights and heights.…”
Section: Illustrative Applicationmentioning
confidence: 99%
“…Despite their potential effectiveness, child safety restraints are frequently misused; thus, increasing the child's risk of enduring serious injuries or death in the event of a MVC (Peden et al, 2008). A nationwide Canadian roadside study found that the rate of correct use of a child safety restraint was approximately 61% for infants (51 year), 67% for toddlers (1-3 years), and only 20% for school-aged children (4-8 years) (Snowdon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%